A systems perspective of parenting : the individual, the family, and the social network - Roberts, Thomas W. (Brooks/Cole, 1994)
A systems perspective of parenting. Human development and parenting. Parent education from a systems perspective. Parenting the infant. Parenting the toddler and preschool child from 2 to 4 years old. Parenting the preschool child from 4 to 6 years old...